Availability for small-scale woody biomass power generation from the view of forest resources in Tochigi Prefecture, Japan. Issue 3 (2nd September 2019) - Yamamoto, Takahisa; Aruga, Kazuhiro; Shirasawa, Hiroaki
ABSTRACT: This study extracted production forests and estimated the annual availability of forest biomass resources under profitable forest management for Japanese cedar and cypress of private and communal forests, as well as national forests, of Tochigi Prefecture, Japan. Production forests were extracted as sub-compartments where expected revenues surpassed all costs, from planting to final harvest, for a 55-year rotation. Then, annual availability of forest biomass resources was estimated on the basis of annual supply potential from production forests. Annual supply potential of timber and forest biomass resources were 1, 070, 234 m 3 and 493, 572 green tons (metric), respectively. Annual availability of timber and forest biomass resources was estimated at 357, 461 m 3 and 149, 808 green tons (metric), respectively. Annual availability of Japanese cedar and cypress was 31.5% and 50.1% of their supply potential in private and communal forests, and 14.4% and 49.6% in national forests, because of higher prices for Japanese cypress and subsidy provision for private and communal forests. In order to maintain sustainable forest management, production forests were extracted with more than 1, 880, 000 JPY/ha (1 USD = 107 JPY on 16 April 2018) profits for a 55-year rotation. As a result, annual availability was estimated at 91, 857 m 3 and 42, 391 green tons (metric), respectively. Since the 2, 500 kWe Nakagawa woody biomass power generation plant consumed 35, 000 green tons/year of forest biomass resources, its demand could be met.